Pelatihan Uji Fisik dan Cita Rasa Kopi Sebagai Instrumen Kontrol Kualitas Kopi dalam Menunjang Wisata Kopi bagi Masyarakat - Luchman Hakim; Sofy Permana; Jati Batoro; Brian Rahardi; Riyan Riyadlun Najih (STKIP Andi Matappa, 2023)
Increasing coffee farmer capacity to produce good coffee bean standar was important. The objective of community service activities were to (1) increase community knowledge about coffee trade prospects and the need for quality coffee, (2) increase community understanding of good coffee farming practices to produce quality coffee beans and (3) increase community understanding of how to recognize coffee bean quality based on basic organoleptic tests. Increasing farmers' knowledge and capacity in coffee production can be done by conducting hands-on training involving strategic partners. Partners involved in this activity include coffee farmers around KPH northern Banyuwangi, Perhutani, local community organizations (MWC NU, Karang Taruna) and coffee observers and activists in Banyuwangi Regency. The activities succeeded in increasing community knowledge about coffee trade prospects and quality coffee. The farmers have understood the market and provide quality coffee beans to meet market expectations. This activity improved the community's understanding of good coffee farming practices to produce quality coffee beans. Good cultivation is crucial to coffee's competitiveness and sustainability. This activity succeeded in improving the community's understanding of how to recognize coffee bean quality. The community gained basic knowledge related to basic organoleptic testing, but these skills need to be improved. Participants have been able to separate beans that are defective, broken, infested with fleas/insects, cracked, contain epidermis, and other characteristics that are not suitable as good quality coffee for processing. Overall the activity received good appreciation from the community, it is hoped that in the future assistance will continue.